2004
DOI: 10.4067/s0716-97602004000100010
|View full text |Cite
|
Sign up to set email alerts
|

Age Dependence of the Levels of Plasma Norepinephrine, Aldosterone, Renin Activity and Urinary Vanillylmandelic Acid in Normal and Essential Hypertensives

Abstract: In the present study the upper reference limits (URLs) for resting plasma norepinephrine, epinephrine, serum aldosterone, plasma renin activity, aldosterone/ renin activity ratio, as well as urinary vanillylmandelic acid in healthy Egyptian normotensive subjects over a range of ages (5-60 yr) were established. There was a significant age effect on plasma norepinephrine, UVMA, serum aldosterone and PRA, whereas a single URL for plasma epinephrine level is satisfactory. In uncomplicated untreated essential hyper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 21 publications
1
12
1
Order By: Relevance
“…This is consistent with findings reported by other authors evaluating normotensive subjects (30) and hypertensive patients (31), but it differs from other author's reports (32), where both ALD and PRA were found to decrease with age.…”
Section: Prc Subgroupcontrasting
confidence: 36%
“…This is consistent with findings reported by other authors evaluating normotensive subjects (30) and hypertensive patients (31), but it differs from other author's reports (32), where both ALD and PRA were found to decrease with age.…”
Section: Prc Subgroupcontrasting
confidence: 36%
“…Another study showed that starting ages 5–10, there was also a drop in plasma levels until the 11–15 age group, before finally moving beyond childrens’ level values to increase until ages 40–60. (Abd‐Allah et al, 2004). Overall these results indicate a u‐shaped progression of the norepinephrinergic levels in plasma with an initial sharp decline at the infant and early toddler age until reaching a lowest point at the start of puberty, followed by a subsequent gentle increase until reaching adulthood.…”
Section: Norepinephrinergic Neurotransmissionmentioning
confidence: 99%
“…Aldosterone is also a part of the RAAS and has potent pro-fibrotic properties [19]. Serum aldosterone levels increase with age and are thought to be the cause of increased myocardial fibrosis in the elderly [20][21][22].…”
Section: Use Of Direct Renin Inhibitorsmentioning
confidence: 99%